Individual Taxpayer Compliance Behavior: Influence of Educational Level, Income Level Ethnic Diversity - Emma Cristina Pandiangan; Kus Tri Andyarini; Dinda Oktavia (Lembaga Penelitian Universitas YARSI, 2024)
The purpose of this study is to investigate how individual taxpayer compliance at PT Trans Indonesia Superkoridor is impacted by factors like as income, education, and ethnic diversity. This study employs quantitative methodology. Primary data were used in this study, and respondents were given questionnaires to complete to collect data. Purposive sampling, with a sample size of 153 respondents, was the sampling strategy utilized. The following tests were used in this study: The F test, the partial test (t test), the heteroscedasticity test, the multicollinearity test, multiple regression analysis, and normality test. The study's findings demonstrate that ethnic diversity and educational attainment have a favorable and substantial impact on individual taxpayer compliance, while the level of income does not have a positive and insignificant effect on individual taxpayer compliance. The managerial implication of these findings is that companies and governments need to consider these factors in designing policies and strategies to improve individual tax compliance. tax education tailored to educational level, and a deep understanding of ethnic diversity to create an environment that supports tax compliance.